Penerapan Model Cooperative Learning Tipe Time Token untuk Meningkatkan Sikap Toleransi dan Hasil Belajar Peserta Didik Pada Pembelajaran Tematik di Kelas IVB SDN 88 Bengkulu Tengah - Sri Dadi; Panut Setiono; Tira Monita (JURIDIKDAS, 2021)
This study aims to improve the attitude of tolerance and learning outcomes of class IVB students at Elementary School 88 Bengkulu Tengah by applying Cooperative Learning model type Time Token assisted by scrapbook media.  This research is a Classroom Action Research.  Subjects in the study amounted to 21 students with 12 female and 9 male.  The research instruments used are observation and test sheets.  The data analysis technique used with the Observation Sheet uses the formula for the average score, the highest score, the lowest score, the difference in scores and the range of values for each criterion.  The test data was analyzed using the formula of average values and classical learning percentage.  The average application of Cooperative Learning model type time token assisted by scrapbook media result of cycle I is 55.8 enough categories and in the second cycle 87.87 very good categories.  The average tolerance attitude result of learning cycle I is 5.72 in the enough category and the second cycle which is 10.23 in the very good category.  The result of learning ips subjects cycle I average was 70.59 with classical completion 57.14%, increase in cycle II which is 77.6 with classical completion 85.71%.  The result of learning ppkn subjects cycle I, average was 69.52 with classical completion 52.38%, increase in cycle II of 78.33 with classical completion 90.4%.  Thus, the implementation of Cooperative Learning model type time token assisted by scrapbook media can increase the tolerance attitude and learning outcomes of students in thematic learning in class IVB Elementary School 88 Bengkulu Tengah.